Gamal (Gliricidia Sepium) Leaf Extract Increase Mortality of Fasciola gigantica In Vitro - Zulianti, Brillia; Hamid, Iwan Sahrial; Yudhana, Aditya; Rahmahani, Jola; Yunita, Maya Nurwartanti; Wibawati, Prima Ayu (Universitas Airlangga, 2021)
Fasciolosis is a disease caused by infection with liver fluke (Fasciola sp). Fasciolosis is a parasitic disease that is important because it can cause high economic losses. The aim of this study was to investigate the effect of gamal (Gliricidia sepium) leaf extract against mortality of Fasciola gigantica in vitro study. In present study was completely randomized design with six treatments and each treatment were divided into four replications. A total of 240 specimens from infected cattles were used in this study. The observation and recording of F. gigantica mortality in all treatments with concentrations of gamal leaf extract P1 (1%), P2 (2%), P3 (3), P4 (4%), K + (Nitroxynil 2%) and K- (physiological NaCl) rate was done in 30, 60, 90, 120, 150, 180, 210 and 240 minutes, respectively. The mortality of F. gigantica was confirmed if there was no movement when triggered by anatomy tweezers then dipped in slightly warm water (50 15í¢„Æ’